Open-access architecture journals in Scopus: analysis of editorial policies - Perdomo, Bexi; Moreno More, César; Flores, Marco (Revista General de Información y Documentación, 2023)
This study aimed to analyze the editorial policies of open-access journals classified in the area of architecture in Scopus. A quantitative study was conducted from a bibliometric perspective. The analysis included: periodicity, genres published, continuous publication, language, authorship, reference style, and article processing charges (APC). English is present in the policies of almost all the journals, the majority of which are from Spain. There was a statistically significant correlation between the APC fee and the quartile of the journal. It is concluded that authors have a wide range of options ranging from those that do not charge APC to those that offer discounts and exemptions for some countries. In addition, a file is provided in which authors have access to all the information on the editorial policies of the journals analyzed so that they can filter the journals according to their needs and select the journal for their open-access publications more easily.
Keywords: Editorial policies; Architecture; Scientific publishing; Open access; Scientific journal